The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3233/shti220970
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on Security and Privacy of Data in IoMT Devices: Performance Metrics, Merits, Demerits, and Challenges

Abstract: The Internet of Medical Things (IoMT) emerges with new trendsetter device applications, where it defines the incorporation of medical devices with the Internet of Things (IoT). The healthcare sector continues to encounter challenging obstacles that have an impact on the quality of treatment provided to patients. To get rid of this problem, IoMT is being deployed to achieve the high reliability and efficiency of the health system. The IoMT devices are superimposed with clinical information as they contain the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…This article is a completely revised and strongly extended version of our contribution to the pHealth 2022 Conference in Oslo [ 1 ]. In the predigital era, patient health data was mostly gathered during face-to-face consultation and manually recorded on paper.…”
Section: Introductionmentioning
confidence: 99%
“…This article is a completely revised and strongly extended version of our contribution to the pHealth 2022 Conference in Oslo [ 1 ]. In the predigital era, patient health data was mostly gathered during face-to-face consultation and manually recorded on paper.…”
Section: Introductionmentioning
confidence: 99%
“…They have blockchains’ immutability, cybersecurity, and interoperability characteristics as those which would facilitate adequate data privacy, storage, and management at minimal cost and risk. Khatiwada and Yang 3 describe IoMT (Internet of medical things) as promising but potentially susceptible to leakage of patient data and having inadequate security and privacy precautions. Blockchain technology would further transform the realm of IoMT, eliminating most of the above-mentioned concerns.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that in the United States, an average patient sees 18.7 different physicians and has 19 medical records during their lifetime. 3 In terms of data privacy, a method to encrypt patient data before sending it to the blockchain was already proposed. 8 …”
Section: Introductionmentioning
confidence: 99%